Optimization of the in-line X-ray phase-contrast imaging setup considering edge-contrast enhancement and spatial resolution - 贾全杰 陈雨 黎刚 姜晓明 (Chinese physics C, 2012)
Employing the approximation theory based on refraction and the definition of the total pointspread-function of the imaging system, the variation in the edge contrast of simple model samples is discussed with different source-to-sample and sample-to-detector distances, which actually means different spatial resolutions of the imaging system. The experiments were carried out with the Beamline 4W1A imaging setup at the Beijing Synchrotron Radiation Facility for simple model and insect samples. The results show that to obtain clear phase-contrast images of biologic tissues for the X-ray in-line imaging setup, with determined parameters such as the size of the X-ray source, the pixel size of the detector and the fixed source-to-sample distance, there is a range of optimized sample-to-detector distances. The analysis method discussed in this article can be helpful in optimizing the setup of X-ray in-line phase-contrast imaging.